TENSES IN TEXT BOOK OF SENIOR HIGH SCHOOL: A SEMANTIC ANALYSIS - Jon Pieter Situmorang; Sri Rezeki Helena Samosir (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This article deals with Tenses in Text Book of Senior High School : A Semantic Analysis. The objective of this article is to find out what functions of tenses in the English Textbook 1st year “TALK ACTIVE”. The article used the qualitative research to carry out the study. In discussing about functions of tenses, the theory of Sukma Setiabudhi (1958) was used to analyze the data. The result shows that in the curriculum, there are four kinds of tenses, they are: (1) simple present tense, (2) simple past tense,(3) simple future tense, and (4) present perfect tense. Meanwhile, in the English Textbook 1st year “Talk Active”, there are nine kinds of tenses, they are (1) Simple Present Tense (2) Simple Past Tense (3) Simple Future Tense, (4) Present Continuous Tense (5) Past Continuous Tense (6) Present Perfect Tense (7) Past Perfect Tense, (8) Present Perfect Continuous Tense (9) Past Perfect Continuous Tense. It is evident that there is a significant inconsistency between the materials presented in the textbook and the syllabus. This disparity is causing unnecessary confusion for both the teacher and the students. The teacher is unable to teach tenses mentioned in the curriculum but not explained in the textbook, which is unacceptable. It is imperative that the materials are synchronized to ensure a seamless learning experience.